Education of Employees and Investment Climate of the Region: The View of the Heads of Enterprises. (12th February 2015) - Ohotina, Alina; Lavrinenko, Olga
Abstract: The investment climate is influenced by different factors: political, economic, social, juridical, ecological, etc. In the modern fast-changing technological world the favourable character of region's investment climate to the great extent depends on the quality of labour resources and investment in human capital that is ensured by formal education and continuous rise of person's professional level. In last decades, information-educational factors, namely, scholarship and the ability to use knowledge as an economic advantage became the key component of the investment climate. Primarily these factors significantly form the potential of enterprises and the potential of the region in general. The aim of the present article is to define how the heads of enterprises evaluate the significance of employees' education in circumstances of external environment factors' influence (which in its turn characterizes the investment climate) on the example of enterprises in Eastern Latvia.